Ginsenoside Rb1 ameliorates Glycemic Disorder in Mice With High Fat Diet-Induced Obesity via Regulating Gut Microbiota and Amino Acid Metabolism - Yang, Xueyuan; Dong, Bangjian; An, Lijun; Zhang, Qi; Chen, Yao; Wang, Honglin; Song, Ziteng (Frontiers in Pharmacology, 2021)
Accumulating evidences suggested an association between gut microbiome dysbiosis and impaired glycemic control. Ginsenoside Rb1 (Rb1) is a biologically active substance of ginseng, which serves anti-diabetic effects. However, its working mechanism especially interaction with gut microbes remains elusive in detail. In this study, we investigated the impact of Rb1 oral supplementation on high fat diet (HFD) induced obesity mice, and explored its mechanism in regulating blood glucose. The results showed that higher liver weight and lower cecum weight were observed in HFD fed mice, which was maintained by Rb1 administration. In addition, Rb1 ameliorated HFD induced blood lipid abnormality and improved insulin sensitivity. Several mRNA expressions in the liver were measured by quantitative real-time PCR, of which UCP2, Nr1H4, and Fiaf were reversed by Rb1 treatment. 16S rRNA sequencing analysis indicated that Rb1 significantly altered gut microbiota composition and increased the abundance of mucin-degrading bacterium Akkermansia spp. compared to HFD mice. As suggested via functional prediction, amino acid metabolism was modulated by Rb1 supplementation. Subsequent serum amino acids investigation indicated that several diabetes associated amino acids, like branched-chain amino acids, tryptophan and alanine, were altered in company with Rb1 supplementation. Moreover, correlation analysis firstly implied that the circulation level of alanine was related to Akkermansia spp.. In summary, Rb1 supplementation improved HFD induced insulin resistance in mice, and was associated with profound changes in microbial composition and amino acid metabolism.